KETERDAPATAN PASIRBESI DI PANTAI BEO DAN SEKITARNYA, KEPULAUAN TALAUD PROVINSI SULAWESI UTARA - Mohammad Akrom Mustafa; Deny Setiady; Udaya Kamiludin (Pusat Penelitian dan Pengembangan Geologi Kelautan, 2016)
Pasirbesi (magnetit) merupakan salah satu hasil pelapukan batuan di daratan dan abrasi pantai oleh pemusatan gelombang dan arus sejajar pantai. Tujuan penelitian menentukan keterdapatan pasirbesi di sekitar Pantai, Kepulauan Talaud, Sulawesi Utara. Metode penelitian meliputi karakteristik pantai, pemercontohan sedimen, analisis megaskopis dan mineral butir disertai fotomikrograf. Tipologi Pantai Beo terdiri dari pantai berkantong pasir dan berbatuan. Endapan Magnetit umumnya menempati pantai berkantong pasir yang sebagian membentuk tanggul gisik. Kadar persentase magnetit (% Fe) antara 0.139 % - 38.11 %. Anomali magnetit dengan kadar kisaran antara 21,414 % dan 38,106 % dijumpai di Pantai Beo, Maririka dan Pantai Batumbalango. Lingkungan keterdapatan magnetit dipengaruhi oleh aktivitas pergerakan tektonik aktif Resen yaitu terangkatnya terumbu karang. Genesa magnetit terkonsentrasi oleh media cair bergerak sebagai endapan plaser pantai yang dipengaruhi oleh fluviatil. Keterdapatan Magnetit diduga berasal dari Batuan Gunungapi Pampini, batuan campuraduk Bancuh Karakelang dan Batuan Ultramafik Kabaruang.Kata Kunci : Magnetit, Karaktersitik pantai, aktivitas tektonik, endapan plaser, sumber batuan, Pantai Beo.Ironsand (magnetite) is one of the mineral potential in some coastal areas of Indonesia, which is related to the presence of andesitic-ultramafic rocks. Therefore Beo coast and its vicinity are then selected as the object of investigation. Magnetite is accumulated as the alochton deposit as the product of rocks weathering in land and coastal abrasion processes are formed by waves and currents parallel to the coast. The methods of investigation include coastal characteristics mapping, positioning, sediment sampling, megascopic and grain minerals analysis with photomicrograph. Coastal characteristics of Beo consist of pocket beach and rocks. Magnetite deposits are usually occupies a pocket beach which is partially formed Berm. The percentage of magnetite content ranging from 0.139% - 38.11%. Anomalies magnetite grading between 21,414 % dan 38,106 % found in Beo, Maririka and the Batumbalango Beach. Magnetite environment is impacted by tectonic movements active in Resen vertically namely the lifting of coral reefs. Magnetite is concentrated on the formation of moving liquid media as placer beach types affected fluvial. The presence of magnetite supposed to be derived from Pampini Volcanics, and mixture of heterogenous rocks Karakelang Melange and Kabaruang Ultramafics. Keywords: Magnetite, coastal characteristics, tectonic activity, placer deposits, source rocks, Beo Beachs